2002
DOI: 10.1136/emj.19.2.122
|View full text |Cite
|
Sign up to set email alerts
|

Emergency management of chest pain: patient satisfaction with an emergency department based six hour rule out myocardial infarction protocol

Abstract: Objective:To measure the level of patient satisfaction with an emergency department based chest pain assessment unit. Design: Structured patient satisfaction surveys. Setting: Inner city university hospital emergency department Participants: 383 consecutive patients aged over 25 years with probable cardiac chest pain of less than 12 hours duration at moderate to low risk of acute myocardial infarction. Intervention: Two structured questionnaires-the first addressing satisfaction with different aspects of the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 12 publications
0
20
1
1
Order By: Relevance
“…This contrasts with previous studies in the UK, which both reported significant improvements in patient satisfaction with CPU care 13 14…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…This contrasts with previous studies in the UK, which both reported significant improvements in patient satisfaction with CPU care 13 14…”
Section: Discussioncontrasting
confidence: 96%
“…At Manchester Royal Infirmary, Richards et al 13 reported high levels of patient satisfaction with the protocol in the ED. The study by Goodacre et al 14 at the Northern General Hospital in Sheffield also found that CPU care was associated with significant improvements in patient satisfaction.…”
Section: The Chest Pain Unitmentioning
confidence: 99%
“…Length of stay (LOS): a shorter LOS would result in a more efficient use of resources, both medical and economical; 2. Patient satisfaction: a multifaceted parameter influencing outcome and quality of care 8,9 ; 3. Anxiety: highly prevalent among chest pain unit (CPU) patients and associated with increased morbidity and mortality.…”
mentioning
confidence: 99%
“…Since then evidence has accumulated that CPC care in the UK is safe, practical, effective, cost-effective, and acceptable to patients. 15,20 Despite this, development has been sporadic. A variety of different approaches to CPC care have been implemented, often poorly funded, and with variable use of diagnostic tests and protocols.…”
Section: Cpc Development In the Ukmentioning
confidence: 97%